(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article analyzes the pioneering initiative of memorialization “Map of the Footprints of Women in Basauri”, promoted in 2009 by the Equality Area of this basque municipality. Focusing on a local experience, from a qualitative perspective and focused on the process, allows to know the dynamics that are generated in the social space around a feminist memory initiative and the vicissitudes that the project went through, and to suggest, in addition, ethical questions, conceptual, political, aesthetic and me- thodological. With the purpose of understanding the particularities, strategies and contingencies that affect the attainment of the objectives and the development of feminist memorialization projects, some considerations are offered that allow understanding the process and contribute to the improvement of tools for the promotion of feminist policies of memory.